2015
DOI: 10.1016/j.yrtph.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological analysis and anti-inflammatory effects of essential oil from Piper vicosanum leaves

Abstract: This study assessed the anti-inflammatory effects of the essential oil from Piper vicosanum leaves (OPV) and evaluated the toxicological potential of this oil through acute toxicity, genotoxicity and mutagenicity tests. The acute toxicity of OPV was evaluated following oral administration to female rats at a single dose of 2 g/kg b.w. To evaluate the genotoxic and mutagenic potential, male mice were divided into five groups: I: negative control; II: positive control; III: 500 mg/kg of OPV; IV: 1000 mg/kg of OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A total of 25 compounds were identified, and the results showed that these species are also rich in sesquiterpenes [24]. Analysis of the essential oil composition of the leaves of Piper vicosanum , with an extraction time of 4 h, identified the sesquiterpenes γ-elemene (14.16%) and α-alaskene (13.44%) and the monoterpene limonene (10.09%) as the majority substances [25]. The α-alaskene substance was not found in any of the nine species analyzed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 compounds were identified, and the results showed that these species are also rich in sesquiterpenes [24]. Analysis of the essential oil composition of the leaves of Piper vicosanum , with an extraction time of 4 h, identified the sesquiterpenes γ-elemene (14.16%) and α-alaskene (13.44%) and the monoterpene limonene (10.09%) as the majority substances [25]. The α-alaskene substance was not found in any of the nine species analyzed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-inflammatory activity was detected by inhibition of leukocyte migration (100, 300, 700 mg/kg) and the protein extravasation into the pleural exudates (700 mg/kg) with no clinical signs of toxicity [ 88 ]. P. vicosanum EO minimized edema formation and inhibited leukocyte migration using the carrageenan-induced edema and pleurisy models at doses of 100 and 300 mg/kg [ 89 ]. The oil displayed a pronounced anti-inflammatory potential, with no acute toxicity or genotoxicity; its main compounds were γ-elemene (14.2%), α-alaskene (13.4%) and limonene (9.1%).…”
Section: Biological Activitiesmentioning
confidence: 99%
“… Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais state, Brazil Aerial parts (HD) α-Pinene (7.2%), 1,8-cineole (15.0%), limonene (40.0%), terpinolene (10.1%) --- [ 153 ] P. vicosanum Yunck. Dourados, Mato Grosso do Sul, Brazil Leaf (HD) Limonene (9.1%), γ-elemene (14.2%), α-alaskene (13.4%) Anti-inflammatory (rat paw edema, 100–300 mg/kg) [ 89 ] P. vitaceum Yunck. Manaus-Caracaraí, Amazonas, Brazil Aerial parts (HD) p -Cymene (12.8%), limonene (33.2%), ( E )-nerolidol (20.6%), caryophyllene oxide (5.2%) --- [ 129 ] P. xylosteoides (Kunth) Steud.…”
Section: Table A1mentioning
confidence: 99%
“…Therefore, it is necessary to develop more effective and less toxic agents (Hoff Brait et al, 2015). The identification of compounds capable of interacting with molecular targets responsible for the amplification of inflammatory processes is a very interesting field of research.…”
Section: Resultsmentioning
confidence: 99%